2006
DOI: 10.1016/j.devcel.2005.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of Cell Surface Material Mediates Cell Plate Formation during Plant Cytokinesis

Abstract: Dividing plant cells perform a remarkable task of building a new cell wall within the cytoplasm in a few minutes. A long-standing paradigm claims that this primordial cell wall, known as the cell plate, is generated by delivery of newly synthesized material from Golgi apparatus-originated secretory vesicles. Here, we show that, in diverse plant species, cell surface material, including plasma membrane proteins, cell wall components, and exogenously applied endocytic tracers, is rapidly delivered to the forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
228
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(246 citation statements)
references
References 83 publications
15
228
2
1
Order By: Relevance
“…In contrast, BFA, which has been extensively used in protein trafficking studies in Arabidopsis root cells (Abas et al, 2006;Dettmer et al, 2006;Dhonukshe et al, 2006;Geldner et al, 2001Geldner et al, , 2003Grebe et al, 2003;Jaillais et al, 2006;Paciorek et al, 2005;Russinova et al, 2004), has a much broader effect on endomembrane compartments, as the TGN, GNOM endosomes, AtSNX1 endosomes/PVC/MVB and Golgi apparatus accumulate in or around the BFA compartments in Arabidopsis root cells (this work and Jaillais et al, 2006; for example). BFA is known to block recycling of PM proteins (Abas et al, 2006;Dettmer et al, 2006;Dhonukshe et al, 2006;Geldner et al, 2001Geldner et al, , 2003Grebe et al, 2003;Jaillais et al, 2006;Paciorek et al, 2005;Russinova et al, 2004). Here, we show that BFA is also capable of preventing the transfer of aleurain-GFP from the BFA compartment to the lytic vacuoles (see Figure 5), suggesting that BFA might have a general inhibitory effect on the transport of proteins from the PVC/MVB to the lytic vacuoles.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In contrast, BFA, which has been extensively used in protein trafficking studies in Arabidopsis root cells (Abas et al, 2006;Dettmer et al, 2006;Dhonukshe et al, 2006;Geldner et al, 2001Geldner et al, , 2003Grebe et al, 2003;Jaillais et al, 2006;Paciorek et al, 2005;Russinova et al, 2004), has a much broader effect on endomembrane compartments, as the TGN, GNOM endosomes, AtSNX1 endosomes/PVC/MVB and Golgi apparatus accumulate in or around the BFA compartments in Arabidopsis root cells (this work and Jaillais et al, 2006; for example). BFA is known to block recycling of PM proteins (Abas et al, 2006;Dettmer et al, 2006;Dhonukshe et al, 2006;Geldner et al, 2001Geldner et al, , 2003Grebe et al, 2003;Jaillais et al, 2006;Paciorek et al, 2005;Russinova et al, 2004). Here, we show that BFA is also capable of preventing the transfer of aleurain-GFP from the BFA compartment to the lytic vacuoles (see Figure 5), suggesting that BFA might have a general inhibitory effect on the transport of proteins from the PVC/MVB to the lytic vacuoles.…”
Section: Discussionmentioning
confidence: 86%
“…It is reasonable to consider that the behaviour of fluorescent proteins reflects the genuine location and dynamics of endogenous proteins, although we cannot exclude the possibility that the fluorescent-tagged proteins might have altered location or stability. We decided to use Arabidopsis root tips as a model system for our analysis, because endocytosis has been extensively studied in this tissue (Abas et al, 2006;Dettmer et al, 2006;Dhonukshe et al, 2006;Geldner et al, 2001Geldner et al, , 2003Grebe et al, 2003;Jaillais et al, 2006;Paciorek et al, 2005;Russinova et al, 2004). To compare the location of YFP-BP80-labelled organelles with compartments of the endocytic pathways, we used the fluorescent dye FM4-64 as an endocytic tracer (Dettmer et al, 2006;Geldner et al, 2003;Grebe et al, 2003;Jaillais et al, 2006;Paciorek et al, 2005).…”
Section: Atsnx1 Endosomes and Pvc Define A Similar Compartment In Aramentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were differences in the membrane resource that produced the septum. In land plants, cell plate formation proceeded mainly by fusion of GVs, resulting in loading of the cell wall materials (Samuels et al 1995), although a recent study showed recruitment of vesicles from endocytosis into the cell plate (Dhonukshe et al 2006). Also, involvement of ER in the formation of the cell plate has been described.…”
Section: Does the Endoplasmic Reticulum Contribute To The Cell Partitmentioning
confidence: 99%
“…The observed 10% decrease in fluorescence could be explained by light stress bleaching the dye during sampling or its instability at room temperature (Bolte et al, 2004). It should be noted that emerging cell plates of dividing cells, previously described for their intense FM4-64 fluorescence (Bolte et al, 2004;Dhonukshe et al, 2006), were not affected by elicitor treatment (Fig. 1A, right).…”
Section: Cryptogein Induces Modifications Of Spectral Properties and mentioning
confidence: 99%